2014
DOI: 10.1111/iej.12304
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of superficial defects in Twisted files and Reciproc nickel–titanium files after use in extracted molars

Abstract: Instrumentation was possible for six root canals with TF files and nine root canals with R25 files before the presence of superficial defects appeared. Differences in the prevalence and development of superficial defects were observed between the TF and R25 files.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
5
22
0
8
Order By: Relevance
“…This finding is in accordance with that of previous studies reporting a fracture rate for single-use Ni-Ti instruments <1% (19,20). In another study, Reciproc R25 instruments have been reported to not fracture until the 12th use for root canal shaping, although it has still been suggested that Reciproc R25 files should be single-use instruments (21). Reciproc instruments also have an S-shaped cross-sectional design, and this design enables superior cutting efficacy (16).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in accordance with that of previous studies reporting a fracture rate for single-use Ni-Ti instruments <1% (19,20). In another study, Reciproc R25 instruments have been reported to not fracture until the 12th use for root canal shaping, although it has still been suggested that Reciproc R25 files should be single-use instruments (21). Reciproc instruments also have an S-shaped cross-sectional design, and this design enables superior cutting efficacy (16).…”
Section: Discussionsupporting
confidence: 90%
“…) and it was also reported that it is possible to perform instrumentation of up to nine root canals using single‐file reciprocating systems with no failure (Caballero et al . ). In this way, the reuse of reciprocating files has had reasonable results as it is a common practice adopted in many countries around the world for economic reasons (Bueno et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Caballero et al . ). Micrographs obtained on new EDM files revealed an irregular and a ‘crater‐like’ surface that is typical superficial morphology of ED‐machined materials.…”
Section: Discussionmentioning
confidence: 97%